NEARPOD WEBSITE STRATEGY IN INCREASING STUDENTS' LISTENING ABILITY - Anisa Turahmah; Djunaidi Djunaidi; Aswadi Jaya (Esteem Journal of English Education Study Programme, 2023)
The main problem of this study was " is there any significant effect on the students' listening achievement after being taught by using Nearpod and those who are not?. The method used in this study was quantitative or quasi-experimental method. The data collected by using written test and online based test on Nearpod Website. The data were analyzed through matched t-test formula and percentage of analysis to find out the effectiveness of teaching listening through Nearpod and Conventional Method. It was found out that the value of t-obtained was 8.12 where the value of the t-table at 0.05 significant level for two tailed with 18 (df) was 2.100. It means that there was significant difference between the result of pre-test and post-test especially the experimental class. It can be stated that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It is indicated that Nearpod Website Strategy could increase students’ listening ability.